Functional neutralization of HIV-1 Vif protein by intracellular immunization inhibits viral replication - Goncalves, J (2015)
Human immunodeficiency virus type 1 (HIV-1) encoded Vif protein is important for viral replication and infectivity. Therefore, Vif is considered to be an important alternative therapeutic target for inhibition of viral infectivity at the level of viral as